P160 What to do when an oesophageal stent fails – relative efficacy of treatment modalities. (19th June 2022) - Frank, Madeleine; Corrigall, Douglas; O'Riordan, Donagh; Gooding, Ian
Abstract : Introduction: Oesophageal stents are the treatment of choice for symptoms of dysphagia in patients with inoperable oesophageal cancer. Whilst this treatment effectively relieves dysphagia, tumour ingrowth and tumour overgrowth are frequent causes of stent failure. This study evaluates the interventions undertaken to treat tumour ingrowth and overgrowth over a thirteen-year period, comparing the relative efficacy of different treatment modalities. Methods: We retrospectively reviewed the outcomes for all patients who had an oesophageal stent inserted at Colchester General Hospital between 2008 and 2020. For the patients with subsequent tumour ingrowth or overgrowth, we analysed the endoscopic re-interventions that were undertaken, comparing placement of a second stent (re-stenting), argon plasma coagulation (APC) and dilatation. A Kaplan Meier survival analysis was used. Requirement for a further gastroscopy was taken as failure of the treatment. If there were no further gastroscopies then the date of death was used as the censor date. Results: 340 patients had a stent inserted for oesophageal cancer. 148 patients required at least one repeat gastroscopy. of these, 62 had endoscopic findings of tumour ingrowth or overgrowth. 41 patients received at least one treatment of APC, 21 patients were re-stented at least once and 13 patients underwent dilatation. The median time interval to need a repeat intervention for patients receiving APC, re-stenting and dilatation were 24, 60 and 31 days respectively. Placement of a second stent was associated with reduced or delayed stent failure compared to the other treatments combined (p<0.002). Conclusions: Tumour ingrowth and overgrowth are common complications of oesophageal stents. Treatment options include APC, dilatation and re-stenting. However there is little evidence to guide which treatment modality is the most effective. This study demonstrates with statistical significance that patients who are treated with re-stenting have a better clinical outcome, defined as a longer time interval until a repeat intervention is required.